THE EFFECT OF FAMILY COMMUNICATION INTENSITY TO THE CHILDREN’S KNOWLEDGE LEVEL OF PANCANA LANGUAGE - Muhammad Hidayatullah; Tuti Bahfiarti; Jeanny Maria Fatimah (Universitas Negeri Makassar, 2020)
This research aims to determine how the effect of family communication intensity atchildren’s knowledge level of pancana language. This research took place in Central Buton, Southeast Sulawesi. The type of research used by researchers is quantitative research methods using multistage random sampling techniques in determining samples. This research uses data collection methods using a questionnaire. In this study, the data collected through the questionnaire was then analyzed by using the SPSS program assistance. The results of the analysis of multiple linear regression tests to test the proposed hypothesis show that the value of Fcount>Ftable (40.9822> 2.402). From the results of the test it was concluded that the intensity of family communication simultaneously or jointly gave a positive and significant influence on the level of knowledge of children in pancana language.